Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014 IEEE Conference on Visual Analytics Science and Technology (VAST) 2014
DOI: 10.1109/vast.2014.7042572
|View full text |Cite
|
Sign up to set email alerts
|

NStreamAware: Real-Time visual analytics for data streams (VAST Challenge 2014 MC3)

Abstract: Figure 1: The image at the top represents a part of the data stream using our sliding slices visualization, which summarizes the stream using sliding windows to provide a summary timeline. The colored histogram at the bottom highlights major events based on extracted keywords and insights of interesting events which were identified by the analyst in real-time. ABSTRACTTo solve the VAST Challenge 2014 MC3 we use NStreamAware, which is our real-time visual analytics system to analyze data streams. We make use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 1 publication
0
28
0
Order By: Relevance
“…Specifically, (Boschetal.2013;Chaeetal.2012) allowmodifying the number of iterations or the number of topics of the LDA model, ) permits the interactive creation and training of the classifiers, (Pritchard et al 2012) involve the user in the selection of POS elements, (Senaratne et al 2014) allows modifyingthe clusterparameters,e.g.,minimumpointsforcluster and radius, whereas ) permit the user to define correlated functions to aggregate geo-tagged tweets. Even more limited, but notable, is the user involvement provided by (Fischer and Keim 2014). In this case, the analyst can remove or reorder some features using a drag and drop interaction and work on the results of the algorithm; however, s/he cannot change directly the parameters of the algorithm.…”
Section: Detailed Comparison Of Research On Microblogging Content Usimentioning
confidence: 99%
“…Specifically, (Boschetal.2013;Chaeetal.2012) allowmodifying the number of iterations or the number of topics of the LDA model, ) permits the interactive creation and training of the classifiers, (Pritchard et al 2012) involve the user in the selection of POS elements, (Senaratne et al 2014) allows modifyingthe clusterparameters,e.g.,minimumpointsforcluster and radius, whereas ) permit the user to define correlated functions to aggregate geo-tagged tweets. Even more limited, but notable, is the user involvement provided by (Fischer and Keim 2014). In this case, the analyst can remove or reorder some features using a drag and drop interaction and work on the results of the algorithm; however, s/he cannot change directly the parameters of the algorithm.…”
Section: Detailed Comparison Of Research On Microblogging Content Usimentioning
confidence: 99%
“…The SA‐related analytical tasks can be synthesized into the following main types: SA1 :Summarize information from heterogeneous streaming data sources for identifying causal relationships behind the changing patterns. SA2 :Take domain knowledge into account and let analysts explore dynamic what‐if scenarios. Based on our survey, we found that very few papers (with the exception of [Erb12, FK14, MJR*11, SBM*14]) address situational awareness scenarios. In Figure , we see one such example where interactive feature selection is used for summarizing and reasoning purposes.…”
Section: Problem Characterizationmentioning
confidence: 99%
“…Designing for enhancing situational awareness [FK14] where exploratory feature selection is used for summarizing multiple time slices. Such exploration and summarization are necessary for stream reasoning and projection of future patterns.…”
Section: Problem Characterizationmentioning
confidence: 99%
“…OCEANS provided multi-level visualization with temporal overview about IP connections and allows participants to collaborate on finding events and targeting attacks. Another interesting work on visual analytics is presented in [11]. It is a system to analyze data streams allowing the analysts to interact with the system and steer the clustering process to reduce the size of data streams to meaningful segments.…”
Section: Related Workmentioning
confidence: 99%
“…From the platforms presented above [7] and [6] are focused on a type of organization and provide very limited visualizations. The works proposed in [9], [10] and [11] focus only some types of threats. OwlSight aims to provide visualization dashboards according the user needs and focus different types of cyber threats to provide an integrated vision around the threat.…”
Section: Related Workmentioning
confidence: 99%